Careering’ – toward radicalism in radical times: Links to human security and sustainable livelihoods - Hopner V; Carr SC (SAGE Publications, 2024)
In this Age of the Anthropocene, the world of work is being radically disrupted by mass precarity, rising wage and income inequality, habitat destruction, and the rise of artificial intelligence. Facing such insecurity, people, we show, are careering toward radical ways of making a living. They range from radical professionals to social media influencing and environmental activism. Human security is fundamentally enhanced by sustainable livelihoods, and we explore ways not only to de-radicalise, but also to accept and embrace radical careering, if and whenever it serves the purpose of making people's livelihoods more sustainable for society, economies, and ecosystems. The article concludes by introducing an Index of Sustainable Livelihoods (SL-I). Success to the successful. The Sustainable Livelihoods Index (SL-I) is designed to be a ‘visible hand’ for end-users, including career counsellors, students, and workers undergoing career transitions, by Corporate Responsibility Officers, and by government ministries supporting just workforce transitions into sustainable livelihoods.
Keywords: Ecosystems; polarisation; Anthropocene; artificial intelligence; radicalism; sustainable livelihoods